2015
DOI: 10.1007/s10113-015-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate impact on Italian fisheries (Mediterranean Sea)

Abstract: Global warming is increasingly affecting marine ecosystems and ecological services they provide. One of the major consequences is a shift in species geographical distribution, which may affect resources availability to fisheries. We computed the mean temperature of the catch (MTC) for Italian catches from 1972 to 2012 to test if an increase of warmer-water species against colder-water ones was observed. We further analysed the relationship among MTC, landings, fishing effort and climatic factors through a Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
(40 reference statements)
2
18
0
2
Order By: Relevance
“…In the present study, although confirming the general relationship, we demonstrated that changing the spatial scale of analysis the situation can be quite different, which could affect also the MTC trend, as reported for the Adriatic Sea by Fortibuoni et al (2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, although confirming the general relationship, we demonstrated that changing the spatial scale of analysis the situation can be quite different, which could affect also the MTC trend, as reported for the Adriatic Sea by Fortibuoni et al (2015).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the level of spatial aggregation, recent studies are commonly based on the Large Marine Ecosystem (LME) scale Gamito et al, 2015), even if the effects of climate changes on fishery can be detected also a smaller scale (Gamito et al, 2012;Fortibuoni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, fishing operations play an important role in shaping community structure as it was also emerging from previous analyses of historical data (Fortibuoni et al, 2010;Barausse et al, 2011). In light of the fact that anthropogenic pressure (here exemplified by fisheries) is the main stressor responsible for the loss of ecosystem resilience (Fortibuoni et al, 2015) to climate-related changes, the process of defining management strategy that policy makers and managers would normally consider are those that reduce fishing pressures that disproportionately degrade the system, or reduce the resilience. However, the present approach could be useful for evaluating management strategies that include deliberate and profitable counteraction of climate effects, such as targeting newly arriving species in a way that maximize or preserve the historical values or other values in the overall social-ecological system.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change associated with global warming has been reported to affect marine ecosystems and fisheries production (Brander, ; Fortibuoni, Aldighieri, Giovanardi, Pranovi, & Zucchetta, ; Hare & Able, ; Kuwahara et al, ; Lacoue‐Labarthe et al, ; Tadokoro, Sugimoto, & Kishi, ). In addition, the increase in water temperature has been reported to induce a poleward shift in fish distribution (Barbeaux & Hollowed, ; Last et al, ; Perry et al, ), leading to changes in annual catch (Teixeira et al, ), fish fauna (Lloyd, Plaganyi, Weeks, Magno‐Canto, & Plaganyi, ; Masuda, ; Mavruk, Bengiil, Yeldan, Mamasorli, & Avsar, ), spawning period (Sims, Wearmouth, Genner, Southward, & Hawkins, ), and spawning ground (Villegas‐Hernández, Lloret, & Muñoz, ).…”
Section: Introductionmentioning
confidence: 99%